Guidance and Counseling in Islam and Moral Development of Higher Institutions’ Students in Nigeria - Adamu, Yusha’u (Al-Iqro', 2024)
This paper intends to discuss the role of Islamic guidance and Counseling to moral Development of higher institutions students in Nigeria. Education is seen as a human right that should be endorsed, sustained and transmitted to the people by the society, education is to a nation what the mind is to the body, is a mechanism through which nation develops. Many agents are responsible for the education of people. Moral development can only said to be achieved if students minimize perpetration of social vices, and should respect others by the virtues of being fellow humans. Guidance and counseling in Islam which is regarded as a helping relationship is intended to acquaint everybody with the nature and functions of an effective Guidance program. The aim is to produce good greater tomorrow who have knowledge and morality. Moral development of our students of higher institutions in this country is very essential factor to consider; this is because in a situation where our greater tomorrow acquires knowledge without morality that knowledge will not serve the purpose it supposes to serve. For this, Islamic guidance and counseling most intervene to save the students and the society by extension.